QURAN-BIBLE VALIDATION IN CONTEMPORARY INDONESIA: SOCIAL MEDIA, RELIGIOUS CONVERSION, AND THEOLOGICAL DEBATE - D.I. Ansusa Putra (UIN Antasari Banjarmasin, 2022)
Religious theological views alter continuously with the context and dynamics of social change. The emergence of digital media and the flow of information has caused a change in the theological views on religious truths and their validation ways. Therefore, this research aimed to explore the theological views and practices of converts in Indonesia who are committed to disseminating validated the Qur'an-Bible relationship in social media as a consequence of their Islamic beliefs. The influence of context and social dynamics on religious theological views was explored by obtaining data through media observations and in-depth interviews with three popular converts on social media, namely Ahmad Kainama, drg. Carissa Grani, and Teressia Pardede. Subsequently, this research concluded that converts to religious theology in Indonesia focus on three basic views, 1) Converts considered Islam as a universal religion and the faith of all prophets and apostles, as Jesus, Moses, and all the bearers of religion in the world are Muslims, 2) Convert judges a historical distortion about Islam and Christianity, 3) Convert claims there is a misinterpretation in understanding Islam and Christianity. This also provided an overview of the impacts that arise due to theological validation in social-religious life by Indonesian converts on social media. This information is expected to contribute to future research as a theoretical-empirical-phenomenological basis about converts and their theological views on social media for the development of relevant investigations.